2017
DOI: 10.1111/jsr.12593
|View full text |Cite
|
Sign up to set email alerts
|

Arousal responses to respiratory events during sleep: the role of pulse wave amplitude

Abstract: The study aims at assessing the changes in electroencephalography (as measured by the A-phases of cyclic alternating pattern) and autonomic activity (based on pulse wave amplitude) at the recovery of airway patency in patients with obstructive sleep apnea syndrome. Analysis of polysomnographic recordings from 20 male individuals with obstructive sleep apnea syndrome was carried out in total sleep time, non-rapid eye movement and rapid eye movement sleep. Scoring quantified the combined occurrence (time range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Previous reports have stated that A-phases, which represented cortical activation, were found in this process. 45 This finding is in agreement with the results of our study.…”
Section: Discussionsupporting
confidence: 94%
“…Previous reports have stated that A-phases, which represented cortical activation, were found in this process. 45 This finding is in agreement with the results of our study.…”
Section: Discussionsupporting
confidence: 94%
“…Fourth, cyclic alternating pattern (CAP) in electroencephalography is the marker of a sleep instability that reflects the brain’s effort to preserve the structure of sleep (Parrino et al, 2012, 2014). The occurrence of CAP was verified to be significantly correlated with the apneas, hypopneas or flow limitation events in OSA patients (Bosi et al, 2018). BZD use in OSA patients may decrease the CAP rate in non-rapid eye movement sleep which results in less resilience to adverse respiratory events.…”
Section: Discussionmentioning
confidence: 97%
“…In their studies on HRV during CAP in healthy subjects and patients with nocturnal front lobe epilepsy (NFLE), Dorantes-Mendez et al [23,24] demonstrated a comparable significant shift towards the low-frequency components of HRV with a more pronounced shift in A3-phases than in A1-and A2-phases. Furthermore, a study on the relation between EEG changes defined by A-phases and the pulse wave amplitude (PWA) after airway obstruction in patients with obstructive sleep apnoea demonstrates a significant correlation between respiratory events combined with A-phases and respiratory events combined with PWA drops [25]. In summary, these findings indicate significant sympathetic activity alterations underpinning the microstructure of sleep.…”
Section: Introductionmentioning
confidence: 86%